2012
DOI: 10.1055/s-0032-1330021
|View full text |Cite
|
Sign up to set email alerts
|

Increase of Peroxisome Proliferator-activated Receptor δ (PPARδ) by Digoxin to Improve Lipid Metabolism in the Heart of Diabetic Rats

Abstract: Increase of peroxisome proliferator-activated receptor δ (PPARδ) expression by digoxin in the heart of diabetic rats has been documented. The present study investigated the mediation of PPARδ in lipid metabolism improved by digoxin in the heart of diabetic rats and in the hyperglycemia-treated cardiomyocytes using the primary cultured cardiomyocytes from neonatal rat. The lipid deposition within the heart section was assessed in diabetic rats by oil red O staining. The fatty acid oxidation genes in cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…8A). To further explore potential mechanisms underlying this TG accumulation, we assessed the expression of enzymes involved in TG synthesis (GPAT1) or hydrolysis (ATGL and HSL) by immunoblotting, as well as transcript levels of PPARd/b, which has been inversely associated with TG content in diabetic hearts (32). Although GPAT1, ATGL, and HSL immunoreactivity were unchanged, we found significant increases in the phosphorylation of HSL on serine 565 (405%; Fig.…”
Section: Mk2 Deletion Protects Against Diabetes-induced Systemic and mentioning
confidence: 86%
“…8A). To further explore potential mechanisms underlying this TG accumulation, we assessed the expression of enzymes involved in TG synthesis (GPAT1) or hydrolysis (ATGL and HSL) by immunoblotting, as well as transcript levels of PPARd/b, which has been inversely associated with TG content in diabetic hearts (32). Although GPAT1, ATGL, and HSL immunoreactivity were unchanged, we found significant increases in the phosphorylation of HSL on serine 565 (405%; Fig.…”
Section: Mk2 Deletion Protects Against Diabetes-induced Systemic and mentioning
confidence: 86%
“…Primary cultures of neonatal rat cardiomyocytes were prepared by the modification of a previously described method [18]. Briefly, under anesthesia with 3% isoflurane, the hearts of 1- to 2-day-old Wistar rats were excised, cut into 1–2 mm pieces, and predigested with trypsin to remove red blood cells.…”
Section: Methodsmentioning
confidence: 99%
“…It has been identified that cardiac agent, such as digoxin and dobutamine, can restore the cardiac contractility in diabetic rats [1012]. Also, cardiac agent improved cardiac contraction in STZ-diabetic rats which is associated with a marked increase in cardiac PPAR δ expression [13].…”
Section: Introductionmentioning
confidence: 99%
“…The impaired cardiac PPAR δ expression could be reversed by anti-hypertrophic treatment [34, 36]. Studies using Western blots also showed protein contents of cardiac PPAR δ are downregulated in doxorubicin-cardiac cytotoxicity [37] and STZ-induced diabetic hearts [38]. In contrast to the above investigations, another study using Western blot showed that cardiac PPAR δ is upregulated in the heart with infarction in rats [39].…”
Section: Pparδ Plays a Crucial Role In Cardiac Pathophysiologymentioning
confidence: 99%
“…Diabetes (type 1 and type 2) and obesity have a strong link to cardiac dysfunction, cardiac hypertrophy and heart failure (see review [5254]). Normalizing cardiac PPAR δ protein improves cardiac fibrosis in rats with streptozocin (STZ)-induced diabetes [37]. Induction of cardiac angiopoietin Like 4 (Angptl4) via PPAR δ activation in the heart is essential in protecting against FA-induced oxidative stress [55], a key mechanism behind diabetic cardiomyopathy.…”
Section: Pparδ Plays a Crucial Role In Cardiac Pathophysiologymentioning
confidence: 99%